Seminar Evaluation of the Use of Antihypertensive Drugs in Hospitalized Patients Suffering From Hypertension in Grandmed Hospital Lubuk Pakam in 2023 - Marbun, Romauli Anna; Nainggolan, Hotdoriska; Wahyuni, Siti; Sihombing, Yanna Rotua; Parinduri, Anggi Isnani (JURNAL PENGMAS KESTRA (JPK), 2023)
Proper treatment is needed to control high blood pressure, including drugs to minimize the strength of blood flow. This study aims to obtain information and knowledge related to the pattern of taking blood flow strength drugs in high blood patients located at Grandmed Lubuk Pakam Hospital 2023. This type of research is an illustrative study using descriptive design and retrospective data. Research shows the use of high blood pressure drugs by hypertensive patients at Grandmed Lubuk Pakam Hospital in 2023 are as follows: Partial accuracy, namely 56 hypertensive patients without complications, right indication 100%, right drug 98.21%, right patient 100%, and right dose 100%. It can be concluded that hypertensive patients at Grandmed Lubuk Pakam Hospital meet the criteria for the right patient, right indication and right dose. The description of the use of high blood pressure drugs at Grandmed Lubuk Pakam Hospital is: (0.1%), candesartan (46.4%), bisoprolol (7.1%), captopril (8.9%), valsartan (7.1%) and furosemide (3.6%). Then community service activities were carried out with the target of 125 Pharmacy students to increase student knowledge related to the use of antihypertensive drugs used in hospitals. The socialization was carried out virtually via zoom and pre-test and post-test were given to assess students' understanding of the service material. The questionnaire is presented in the form of a googleform as an assessment of feedback on the results of socialization materials issued after the activity is completed. The activity was also filled with responses and questions and answers with service participants. The conclusion obtained is that 87% of students understand the use of hypertension drugs very well, 12% understand well, and 1% understand the use of hypertension drugs enough.